KONSEP NASIKH MANSUKH DI ERA MODERN DALAM PRESPEKTIF IMAM AL-TABATHABA’I - Risa Fadhilah (Isti`dal : Jurnal Studi Hukum Islam, 2021)
Nasikh-mansukh is one of the controversial branches of Al-Quran science. This is because there are at least two conflicting views regarding the existence of these nasikh-mansukh, some scholars are of the view that there are nasikh-mansukh in the Qur'an, while some scholars have the opposite view, that there is no nasikh-mansukh in the Qur'an. an. Coupled with the rapid development of the times so that many try to reconstruct and even deconstruct the Nasikh-Mansukh theory. Nasikh-mansukh as a branch of Qur'anic science in maintaining legal knowledge so that it does not conflict with human benefit. This study tries to compare the nasikh-mansukh theory by Imam At-thabathaba'I with the current state of the modern era. The concept of nasikhmansukh put forward by Imam Tabataba'i prioritizes the benefit paradigm, which distinguishes the views of Imam Tabataba'i from other scholars. So that the author is interested in studying the theory because it is considered appropriate to the conditions of modern times as it is today, and we can understand the position of the texts in the Qur'an